KAJIAN PEMBERIAN SISA PENGGILINGAN PADI DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN VEGETATIF TANAMAN SAWI HIJAU (Brassica juncea L.) - Rahmadina Rahmadina (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
Green mustard plants (Brassica rapa var. Parachinensis L.) are plants that have a source of vitamins and minerals. The purpose of this study was to determine the effect of the concentration of rice grinder and liquid organic fertilizer on the vegetative growth of mustard greens (Brassica juncea L.), to determine the effect of a mixture of Giving POC with plant growth on mustard plants and to determine the effect of a combination of POC and planting media mixture on the growth of mustard plants. This research was conducted in February to May 2020, Jalan Ekarasmi gg. ekanusa in the Kelurahan Gedung Johor, Medan Johor District, Medan City with a height of Â± 30 m above sea level using a Random Factorial design consisting of 2 factors and 3 replications. The results showed that the POC concentration did not show a significant effect on plant height, number of leaves, leaf length, leaf width, leaf area, wet weight and chlorophyll of mustard plants, but visually the highest results were obtained at P2 treatment (30 cc / L water ) followed by P1 (15 cc / L water) and the lowest in P0 treatment (without POC), the planting media mixture showed a very significant effect on plant height at 7 and 14 HST and had no significant effect on all other observation variables. The highest yield was obtained in the treatment of M0 (Top Soil Soil) followed by M1 (Top Soil and Rice Husk Mixture) and M3 (Top Soil and Rice bran Mixture) and the lowest in M2 (Top Soil and Bran Soil) mixture, POC and the planting media mixture showed a very significant effect on the plant height variable at 14 HST and the amount of chlorophyll at harvest and had no significant effect on other variables. The best results were obtained on M3 P2 (Top Soil and Rice bran Mixture; P2 (POC concentration of 30 cc / L water).)Keywords: leftover rice mill, liquid organic fertilizer, mustard plant, vegetable pesticide.